The economics of broiler contract growing in Iloilo - Leda, Robert D. . (CAS, UPV, Miag-ao, Iloilo, 1996)
This study described the socio-economic characteristics of broiler contract growers and assessed the economic performance of the broiler contract growing production. A profile described the living conditions of the growers/owners and costs and returns analysis was used to analyzed the economic performance of the venture., The research showed the socio-demographic characteristics of broiler contract growers describing their age, profession, educational attainment, civil status and gender. Moreover, the research showed the characteristics of broiler contract grower farms, their management and production practices, problems and their possible solutions. Costs and returns analysis showed the average total cost in broiler contract growing was P65,483.82 or P 7.2058/bird. Fixed, variable and opportunity cost accounted for 32.86, 50.28 and 16.86 per farm, respectively, while 35.85, 45.61 per bird, respectively. The average price rate per bird in terms of kilo in their pricing system was P7.71. However, with incentives, RFM-Swift bought the broilers from the contract growers at an average price of P 9.47/bird. The average total revenue reported by the growers was P95,652.22. Broiler contract growers realized and average gross profit of P 41,207.83 or P3.76/bird and an economic profit of P 30,168.18 or P 2.27/bird.
Thesis (Undergraduate, Bachelor of Arts in Economics-Management) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Broiler Contract Growers -- Birds